CONSIDERATIONS ABOUT THE INFLUENCE OF PHYSICAL CONDITIONING AND CLIMATIZATION IN FLUID LOSS (Fiep Bulletin - online, 2015)
The intention of this study is to evaluate the level of dehydration that university students may reach in a session of outdoor exercises with the duration of one hour and to verify the relation between the tax of sudorese, level of physical aptitude and acclimatization. A group (n=25) of men and women who kept regular physical activity  were submitted to make one hour of physical exercises in a track of running  a circuit training (CT). The group was divided in two sub-groups, hydrated (GH) and not hydrated (GNH). Each integrant of the GH ingested 200ml of water in the beginning of the CT and every 15minuts during the total time of exercises. The GNH did not have any type of hydration during the CT. The analyzed variable  were the initial  body weight(BW), the PC after the CT and the difference enters the values of the PC. The average of PPC for GH and GNH was respectively 185,71g and 745,45g. PPC values of 1,1Kg were found in some individuals of the GNH, while in the GH some individuals had gained 100g of corporal weight. The average of PPC for men of the GH was 131,19g and for the women of the GH was 42,86g. The average of PPC of the men of the GNH was  1066,67g and for women  was 625g. The values obtained suggests a bigger secretory  activity of the glands sweat in trained men and women. Comparing men and women, the men had presented greater gland production.
Keywords: .